2018
DOI: 10.1002/qua.25616
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the spin state of diphenylcarbene via halogen bonding: A theoretical study

Abstract: Halogen bonding has recently become an effective tool to control the spin state of reactive carbenes. In this work, a series of the complexes of diphenylcarbene (DPC) that has a triplet ground state with several halogen bond donors RX were theoretically studied, and in particular, the influence of the formation of halogen bonding on the spin state of DPC was extensively explored. The spin flip depends on the difference of halogen bond energies between triplet and singlet, that is, when the difference is large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Although a wide range of computational studies have previously investigated the differential stabilization of the spin states of carbenes by means of implicit solvation models, only a few took into account the role that direct intermolecular interactions play in this context. ,, In particular, Standard recently applied correlated wavefunction-based methods to calculate E S–T values of several carbenes as well as of their hydrogen-bonded complexes with water and methanol. It was found that in all cases hydrogen bonding selectively stabilizes the singlet state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a wide range of computational studies have previously investigated the differential stabilization of the spin states of carbenes by means of implicit solvation models, only a few took into account the role that direct intermolecular interactions play in this context. ,, In particular, Standard recently applied correlated wavefunction-based methods to calculate E S–T values of several carbenes as well as of their hydrogen-bonded complexes with water and methanol. It was found that in all cases hydrogen bonding selectively stabilizes the singlet state.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of charge transfer is significantly reduced in the triplet state, which qualitatively explains the observed differential spin-state stabilization. Halogen-bonding interactions with singlet carbenes have also been studied computationally in a number of studies, , but, to the best of our knowledge, a comparative study of the effect of such intermolecular interactions on the stabilization of singlet and triplet halogen-bonded complexes of carbenes has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al [39] further discussed the in uence of the formation of halogen bond on the spin state of DPC and the decisive factors in spin slip via density functional theory (DFT) calculations.…”
Section: Introductionmentioning
confidence: 99%